2013
DOI: 10.1016/j.jvs.2013.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional area for the calculation of carotid artery stenosis on computed tomographic angiography

Abstract: These data support the use of CTA as an accurate method of calculating carotid artery stenosis based on agreement with Strandness criteria applied to CDUS velocities. When additional imaging beyond CDUS is necessary, we report no significant difference between diameter and CSA measurements obtained from CTA for preoperative evaluation of carotid disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Carnicelli et al tested the accuracy of CTA using CDUS as a surrogate for true stenosis, and came to the conclusion that there is no significant difference between diameter and area measurements [6]. Bartlett et al, testing diameter and area measurements, concluded that carotid stenosis quantification based upon the narrowest diameter reliably predicts the more precise area measurements [7].…”
Section: Discussionmentioning
confidence: 99%
“…Carnicelli et al tested the accuracy of CTA using CDUS as a surrogate for true stenosis, and came to the conclusion that there is no significant difference between diameter and area measurements [6]. Bartlett et al, testing diameter and area measurements, concluded that carotid stenosis quantification based upon the narrowest diameter reliably predicts the more precise area measurements [7].…”
Section: Discussionmentioning
confidence: 99%
“…The stenosis of the contralateral carotid artery was determined in CTA and mainly obtained from axial images using the North American Symptomatic Carotid Endarterectomy Trial equation [29]. All centers used a bolus-triggering technique with region of interest in the ascending aorta at the beginning of the aortic arch.…”
Section: Methodsmentioning
confidence: 99%
“…UoW criteria. The UoW criteria [10][11][12] combine PSVs and end-diastolic velocities to classify stenosis. A stenosis of 50% to 79% is indicated by a PSV >125 cm/s and an end-diastolic velocity <140 cm/s; a stenosis $80% is indicated by a PSV >125 cm/s and an end-diastolic velocity $140 cm/s.…”
Section: Dusmentioning
confidence: 99%